(3CKQ GdJaGYd Hjf feW GdEHMGQ HcGFfGJ GdJYde hGdCSdhH GdeYQai Ydi OGaYjI GdGfLGR hHbGA CKQ GdJYde dOi JdGejP GdeQMdI GdEYOGOjI (B/s - (3fjajf Ydi CMeO YHO GdeLjO,s; (3Sdhi aJMi eMehO GdeUQjs; (3QGfjG EHQGgje CMeOs (2024)
(3gOa GdHMK GdMGdi Edi GdJaGYd Hjf feW GdEHMGQ (B( (3GdgQei (B/ (3GdTHci (B) (3HcGFfGJ GdJYde GdQbejI hCKQg Ydi OGaYjI GdEfLGR hHbGA GKQ GdJYde dOi JdGejP GdeQMdI GdGYOGOjI , Je EYOGO COhGJ GdbjGS (B((3OGaYjI GdEfLGR(B. (3HbGA GKQ GdJYde (B) (3, hJhUdJ Cge GdfJGFL Edi Jahb GdeLehYI GdJLQjHjI GdJi OQSJ HfeW GdEHMGQ GdgQei hGdCSdhH GdeYQai GdeYJeO hPdc ai fJGFL GdJWHjb GdHYOi ddGNJHGQ GdJMUjdi, hGXgQJ GdOQGSI Yf YOe hLhO aQhb PGJ OdGdI GMUGFjI dcd ef feW GdEHMGQ (B((3gQei (B/(3THci(B) (3HcGFfGJ GdJYde GdQbejI hGdGSdhH GdeYQai (B((3eYJeO(B/(3eSJbd(B) (3ai HWGbI GdedGMXI, ai Mjf JahbJ GdeLehYI GdJLQjHjI GdJi OQSJ HfeW GdEHMGQ GdTHci hGdCSdhH GdeYQai GdeYJeO ai fJGFL GdJWHjb GdHYOi debjGS OGaYjI GdEfLGR (B.s
The aim of the current research is to investigate the interaction between the style of browsing (hierarchical/network) with digital learning objects and its impact on achievement motivation and the persistence of the learning effect among middle school students. Measurement tools were prepared (achievement motivation. The persistence of the learning effect), and the most important results reached the superiority of the experimental group that was studied. In the hierarchical navigation style and the approved cognitive style in the results of the post-application of the achievement test, the study showed that there were no statistically significant differences for both the navigation style (hierarchical/network) with digital learning objects and the cognitive style (dependent/independent) in the observation card, while the group excelled. The experimental study that was studied using the network navigation method and the cognitive method adopted in the results of the post-application of the achievement motivation scale.
(3CWQhMI (B((3eGLSJjQ(B)-(3LGeYI GdbGgQI, (B2024. s
(3HHdjhLQGajG(B: (3UaMGJ (B143-152.s
(3UOQ CjkVG cbQU eOeL(B.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3JcfhdhLjG GdJYdjes; (3CfeGW GdEHMGQ s -- (3cGFfGJ GdJYde GdQbejIs -- (3GdCSdhH GdeYQais -- (3OGaYjI GdEfLGRs -- (3HbGA GKQ GdJYde s